ANALISIS KINERJA SOSIAL DAN KINERJA KEUANGAN LEMBAGA KEUANGAN MIKRO (LKM) USAHA EKONOMI DESA-SIMPAN PINJAM (UED-SP) CANDI MAKMUR KABUPATEN INDRAGIRI HULU - Syofian '; Ahmad Rifai; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study to analyze the performance of the social and financial performance over the period 2009-2013 were conducted in rural microfinance institutions (UED-SP) Candi Makmur. Social performance analysis using MIX Market performance indicators, and financial performance analysis method using 17 ratio with Pearls. Social performance analysis show has achieved its mission and social purpose indicated by the indicator development revolving loan volume of 56.37 percent, the development of the highest revolving loan is trade 58.36 percent and the number of poor borrowers 260 people with poor loan growth 116.3 percent. Activity and increased internal system is shown by the staff productivity indicator for the number of borrowers, loan volume and ratio of staff incentives. Increased output and outcome in dicators shown by the borrower based on gender, the ratio of borrowers by business sector and the ratio of the number of poor borrowers. Financial performance analysis shows the ratio of 17 pearls were analyzed, 7 ratio is under ideal conditions the ratio of current assets, loans from the outside, the capital of institutions, non-productive assets, operating costs, asset growth and the growth of outstanding loans. which is not ideal for the ratio is the ratio of the risk reserve fund for loans negligence 1-12 months and over 12 months, outstanding loans, savings shares, non perfoaming loan, income from loans, net income, current assets do not generate, growth stock savings and growth institutional capital. Keywords: Financial Performance, Microfinance Institution, Social Performance, UED-